'Do It Yourself' in the parent–professional partnership for the assessment and diagnosis of children with autism spectrum conditions in Hong Kong: A qualitative study. (October 2014) - Ho, Hilda SW; Yi, Huso; Griffiths, Sian; Chan, Dorothy FY; Murray, Stuart
Timely and appropriate care for children with autism spectrum conditions is affected by the interaction between healthcare professionals and parents. Despite the importance of the parent–professional partnership, there is a dearth of cultural-specific data on parent–professional partnership in the Chinese context. We conducted 10 in-depth life-history interviews with parents of children with autism spectrum conditions in Hong Kong who were diagnosed during preschool years. Using an interpretative phenomenological analytic method, five themes were constructed to represent the context of parent–professional partnership in Hong Kong along the pathway of seeking a diagnosis: (a) access to the assessment and diagnosis of autism spectrum conditions, (b) multiple procedures of assessment, (c) consultation prior to diagnosis and assessment, (d) communication of diagnosis and assessment result and (e) post-assessment isolation. Parental narratives highlight the important domains of parent–professional partnership and reflect the complexity of diagnosis and the lack of a cohesive system. For many parents, the assessment procedure was marred by a series of obstacles, which were further exacerbated by a poorly developed parent–professional partnership. Suggestions for parent–professional partnership development include establishing an evidence-based best practice guideline for Hong Kong, creating pre-assessment information workshops for parents to attend and equipping professionals with knowledge about autism spectrum conditions and enhanced communication skills.